Gene expression profiling of astaxanthin and fatty acid pathways in Haematococcus pluvialis in response to different LED lighting conditions. (February 2018) - Ma, Ruijuan; Thomas-Hall, Skye R.; Chua, Elvis T.; Alsenani, Faisal; Eltanahy, Eladl; Netzel, Michael E.; Netzel, Gabriele; Lu, Yinghua; Schenk, Peer M.
Graphical abstract: Highlights: LEDs provide useful tools to stimulate Haematococcus astaxanthin biosynthesis. High intensity white and blue LED significantly increased astaxanthin content. Total fatty acid content was induced by high intensity white LED. Astaxanthin and fatty acid biosynthesis genes are regulated by different LEDs. Five H. pluvialis dgat genes were identified and dgat2a was induced by blue LED. Abstract: Haematococcus pluvialis is a green microalga of major interest to industry based on its ability to produce large amounts of astaxanthin. Biosynthesis of astaxanthin and its mono- and di-esters was significantly stimulated under 150 μmol m −2 s −1 of white LED (W-150) compared with lower light intensities, but the highest astaxanthin amounts were produced under 70 μmol m −2 s −1 of blue LED (B-70). Transcripts of astaxanthin biosynthesis genes psy, crtO, and bkt2 were upregulated under W-150, while psy, lcy, crtO, and crtR-B were upregulated by B-70. Total fatty acid content and biosynthesis genes fata and all dgat genes were induced under W-150, while C18:3n6 biosynthesis and dgat2a expression were specifically stimulated by B-70 which was correlated to astaxanthin ester biosynthesis. Nitrogen starvation, various LEDs and the identified upregulated genes may provide useful tools for future metabolic engineering to significantly increase free astaxanthin, its esters and fatty acid precursors in H. pluvialis .